Mengubah Tradisi Lisan Masyarakat Menjadi Tradisi Tulisan: Menjaga Eksistensi Negeri Adat di Negeri Samasuru Kecamatan Teluk Elpaputih Kabupaten Maluku Tengah - Matatula, Syane; Titely, Elsina; Alfons, Christwyn R. (AJAD : Jurnal Pengabdian kepada Masyarakat, 2024)
The country is a territorial area of settlement of indigenous peoples who have built interactions with each other since ancient times and over a long period to form a culture as a tradition of customs. The country and its traditions and customs constitute an identity for both the individual and the collective community of its adherents. Apart from that, transforming previous generations' knowledge through oral storytelling will significantly contribute to the low level of understanding and shift in the meaning of traditional values. This Community Service aims to provide knowledge or experience to the community about the importance of maintaining traditional identity for future generations by transforming traditional understanding of the country's customs on Seram Island, Maluku, in writing so that their substantial meaning can be known and understood well. Results of Community Service It is hoped that it can contribute to the sustainability of the traditional values of Samasuru Country in particular and other traditional areas in Maluku and Indonesia in general.